XII Legal-Historical Colloquium “The legal education from Beirut to Bologna. On the jubilee of the 10th anniversary of the Faculty of Law and Administration of Opole University”, Brzeg, 10–11 May 2016 - Szymański, Andrzej (The Opole Studies in Administration and Law, 2016)
Report from the XII Legal-Historical Colloquium “The legal education from Beirut to Bologna. On the jubilee of the 10th anniversary of the Faculty of Law and Administration of Opole University”,